Strategi Pemecahan Masalah Neurosis Depressif Dalam Pelayanan Pastoral Kontekstual - Harming Harming; Ayu Rotama Silitonga (Shalom: Jurnal Teologi Kristen, 2021)
Pastoral care cannot be separated from counseling services as a form of guidance for people who have problems or commonly referred to as counselees. The problem discussed by the author is the problem of depressive neurosis. Depressive neurosis is a problem that occurs in a person's psyche without knowing the cause. In solving the problem of depressive neurosis, a good strategy is needed so that this problem can be solved. The purpose of this writing itself is so that the servant or counselor can understand and know what strategies are suitable to be used in helping to solve the problem of depressive neurosis in contextual pastoral care. The method used is the Literature method by observing books and journals or articles to support writing. Build a good relationship with the counselee, involve and direct the counselee's family to help the counselee, encourage the counselee to know himself, listen to the counselee well without guessing the problems experienced, provide support to the counselee, and provide opportunities and guide the counselee to take a way out. of the problem. Thus, the authors hope, the strategies described can be used in pastoral care to solve the problem of depressive neurosis.